Systematic Literature Review: Technology-Based Media that Support Critical Thinking Skills in Mathematics Learning - Hartati, Hartati; Hidayanto, Erry; Sisworo, Sisworo (Media Pendidikan Matematika, 2026)
This study extensively reviews research on technology-based media used to support critical thinking skills in mathematics learning over the past ten years using accurate Scopus data. This study used a systematic literature review that includes six different steps, which analyzes 8 English language scientific articles published between 2016 and 2025. From the results of the selection of 8 articles that were analyzed descriptively qualitatively based on critical thinking skills, mathematics learning technology media in supporting critical thinking. Based on the research criteria, it is seen that research began in 2020-2025, with a dominance in 2022 and 2024 with 2 articles each. Most of the research was conducted at the junior high and senior high school levels, with the most prominent focus on algebra. This research is dominated by Jawa Island with 6 articles and experimental research methods and research & development dominate. In addition, technology based media referred to in learning include Interactive Digital Worksheets, Android-based Carom Game Comics, YouTube, the MathCityMap application, Assisted Video Animation, Augmented Reality, Smart Math learning media based on Articulate Storyline, and GeoGebra. This media explains the relationship between critical skills and mathematics learning, particularly in improving critical thinking skills. This research provides an opportunity to further explore technology-based media that have not yet been utilized.